Development of a nanoemulsion bioherbicide and its herbicidal efficacy - Hasan, Mahmudul; Mokhtar, Anis Syahirah; Motmainna, Mst; Ahmad-Hamdani, Muhammad Saiful (John Wiley and Sons, 2025)
BACKGROUND: Bioherbicide applications are environmental-friendly approaches to control weeds toward sustainable agriculture. Hence, the current research focused on developing a ready-to-use nanoemulsion bioherbicide from the current less economical WeedLock bioherbicide, furthermore evaluating its weed control efficacy. Nanoemulsion composition comprised 2-undecanone (active ingredient), Termul 5030, POE(20)SMO, and water. The selected formulations were incorporated with 5% active ingredient. RESULTS: Among the 11 formulations tested, three formulations (WLRF7, WLRF9, and WLRF11) showed remarkable stability, in centrifugation, storage stability, and thermostability. Furthermore, screening for weed control efficacy on Ageratum conyzoides L., Eleusine indica (L.) Gaertn. and Cyperus iria L. at 1345.50 L ha−1 (WeedLock recommended rate) WLRF9 formulation exhibited a greater efficacy of 98.39% than WLRF7 (83.90%) and WLRF11 (91.31%). In the dose–response experiment, at the recommended rate, 98.16%, 98.25%, and 98.38% control efficacy were produced by the WLRF9 formulation, glufosinate-ammonium, and glyphosate isopropyl-amine, respectively. CONCLUSION: Evidently, the new bioherbicide formulation (WLRF9) has shown excellent efficacy and potential to control weeds.